The lack of genetic variation underlying thermal transcriptomic plasticity suggests limited adaptability of the Northern shrimp, Pandalus borealis - Leung, Christelle; Guscelli, Ella; Chabot, Denis; Bourret, Audrey; Calosi, Piero; Parent, Geneviève J. (Frontiers in Ecology and Evolution, 2023)
Genetic variation underlies the populations’ potential to adapt to and persist in a changing environment, while phenotypic plasticity can play a key role in buffering the negative impacts of such change at the individual level. We investigated the role of genetic variation in the thermal response of the northern shrimp Pandalus borealis, an ectotherm species distributed in the Arctic and North Atlantic Oceans. More specifically, we estimated the proportion transcriptomic responses explained by genetic variance of females shrimp from three origins after 30 days of exposure to three temperature treatments. We characterized the P. borealis transcriptome (170 377 transcripts, of which 27.48 % were functionally annotated) and then detected a total of 1 607 and 907 differentially expressed transcripts between temperatures and origins, respectively. Shrimp from different origins displayed high but similar level of transcriptomic plasticity in response to elevated temperatures. Differences in transcript expression among origins were not correlated to population genetic differentiation or diversity but to environmental conditions at origin during sampling. The lack of genetic variation explaining thermal plasticity suggests limited adaptability in this species’ response to future environmental changes. These results together with higher mortality observed at the highest temperature indicate that the thermal niche of P. borealis will likely be restricted to higher latitudes in the future. This prediction concurs with current decreases in abundance observed at the southern edge of this species geographical distribution, as it is for other cold-adapted crustaceans.